The Development of E-Learning Media Based Moodle to Increase Science Development and Islamic Studies in STAIN Gajah Putih - Leni Agustina Daulay; Firmansyah Firmansyah; Rahmanita Zakaria (AT-TA'LIM, 2017)
Along with the development of information technology, which more rapidly, the need of a concept and mechanism of Information Technology-based learning becomes inevitable. Then, concept known as e-learning take affect transformation of occurs conventional education into digital form, both the content and the system that is bridged by the technology of internet. The concept of e-learning gives the possibility of interaction between lecturers and students, either the students in the classroom or outside the classroom intensively. This study aimed to obtain e-learning media based Moodle is effective to support the development of science and Islamic studies in Gayo through a series of development process. The finding of the study showed that e-learning based Moodle was conducted by using 4-D model (Four D Model). The results also showed that of development activities are: (1) e-learning media in Gayo which can be seen in www.elearning-gayobelajar.com and (2) the use of guide books for lecturers and teachers. The Finding also indicated that the development of E-learning based Moodle is reliable or has a high level of reliability if t is used in university.